2018
DOI: 10.1515/jpm-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

From single-case analysis of neonatal deaths toward a further reduction of the neonatal mortality rate

Abstract: Background The infant mortality rate (IMR), a key indicator of the quality of a healthcare system, has remained at approximately 3.5‰ for the past 10 years in Germany. Generic quality indicators (QIs), as used in Germany since 2010, greatly help in ensuring such a good value but do not seem to be able to further reduce the IMR. The neonatal mortality rate (NMR) contributes to 65-70% of the IMR. We therefore propose single-case analysis of neonatal deaths as an additional method and show an efficient way to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Further, KLS subjects with TRANK1 polymorphism have reported increased birth difficulties (summarized in Dataset S5). We hypothesize that improved perinatal outcomes that have occurred in the past 50 years may explain this tendency (34)(35)(36)(37)(38)(39); https://www.cdc.gov/nchs/data/nvsr/nvsr56/nvsr56_10.pdf; https://mchb.hrsa.gov/chusa14/health-status-behaviors/infants/infant-mortality.html).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, KLS subjects with TRANK1 polymorphism have reported increased birth difficulties (summarized in Dataset S5). We hypothesize that improved perinatal outcomes that have occurred in the past 50 years may explain this tendency (34)(35)(36)(37)(38)(39); https://www.cdc.gov/nchs/data/nvsr/nvsr56/nvsr56_10.pdf; https://mchb.hrsa.gov/chusa14/health-status-behaviors/infants/infant-mortality.html).…”
Section: Discussionmentioning
confidence: 99%
“…Further, KLS subjects with TRANK1 polymorphism have reported increased birth difficulties (summarized in Dataset S5 ). We hypothesize that improved perinatal outcomes that have occurred in the past 50 years may explain this tendency (34-39); https://www.cdc.gov/nchs/data/nvsr/nvsr56/nvsr56_10.pdf; https://mchb.hrsa.gov/chusa14/health-status-behaviors/infants/infant-mortality.html). The TRANK1 birth difficulties relationship was also confirmed in the independent replication sample, where we found that only the subset of KLS patient reporting birth difficulties had a significant TRANK1 association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With this approach, it is now possible to compare databases on an international level, and country-specific annotations with only one uniform query language, such as German or English, could be implemented. A first application, in which neotalogic epicrises were analysed with regard to avoidable infant mortality, has already proved successful [35].…”
Section: Discussionmentioning
confidence: 99%
“…Through the years 1990 to 2020 neonatal deaths dropped from 5million to 2.4 million. However, the rate of reduction of neonatal mortality is still slower than postneonatal mortality (Sander, A., Wauer, R., & WHO. 2020).…”
Section: Introductionmentioning
confidence: 99%